2015
DOI: 10.1051/ocl/2015061
|View full text |Cite
|
Sign up to set email alerts
|

AceDoPC, a structured phospholipid to target the brain with docosahexaenoic acid

Abstract: -AceDoPC r is a structured phospholipid or acetyl-LysoPC-DHA made to prevent docosahexaenoic acyl migrating from the sn-2 to sn-1 position of the phospholipid, however keeping the main physical-chemical properties of LysoPC-DHA. As previously shown for LysoPC-DHA, AceDoPC r allows DHA crossing a re-constituted bloodbrain barrier with higher efficiency than non-esterified DHA or PC-DHA. When injected to blood of rats, AceDoPC r is processed within the brain to deliver DHA to phosphatidyl-choline and -ethanolami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It has been suggested that the brain maintains DHA levels primarily via the uptake of DHA from lipids in circulating blood through the blood-brain barrier, rather than possessing particularly active endogenous biosynthesis, which is reportedly lower in in the brain compared to other tissues (DeMar et al 2006). There is evidence that a major transporter of DHA to the brain is in the form of lyso-phosphatidylcholine (sn 2-DHA-PC), which is taken up by a specific transporter known as MFSD2A, located in the blood brain barrier (Lagarde et al 2016). Consequently, a mounting number of studies are focusing on the role for DHA in brain development and the prevention of neurodegenerative and neuropsychiatric disorders.…”
Section: Dha In the Brain And Visual Functionmentioning
confidence: 99%
“…It has been suggested that the brain maintains DHA levels primarily via the uptake of DHA from lipids in circulating blood through the blood-brain barrier, rather than possessing particularly active endogenous biosynthesis, which is reportedly lower in in the brain compared to other tissues (DeMar et al 2006). There is evidence that a major transporter of DHA to the brain is in the form of lyso-phosphatidylcholine (sn 2-DHA-PC), which is taken up by a specific transporter known as MFSD2A, located in the blood brain barrier (Lagarde et al 2016). Consequently, a mounting number of studies are focusing on the role for DHA in brain development and the prevention of neurodegenerative and neuropsychiatric disorders.…”
Section: Dha In the Brain And Visual Functionmentioning
confidence: 99%
“…Furthermore, it is integral to membrane trafficking and molecule transportation. LysoPC composed of C22:6 (at the sn-2 position) has been demonstrated to be more effective than C22:6-free fatty acids in crossing the blood-brain barrier [67].…”
Section: Phosphatidylcholinementioning
confidence: 99%
“…More recently, to avoid FA migration from the sn-2 to the sn-1 position in LPC-DHA, the sn-1 position was blocked with an acetyl group, leading to the formation of a phospholipid named 1-acetyl-2-docosahexaenoyl-glycerophosphocholine or AceDoPC ® ( Figure 3 ). AceDoPC ® is considered to be a stabilised form of LPC-DHA [ 33 , 34 , 35 , 36 ].…”
Section: Structure and Biosynthesis Of Lpcmentioning
confidence: 99%